The use of poliheksamethyleneguanidine (phmg) salts in alcohol production from starch-containing raw materials - Boiko, Petro; Bondar, Nikolai; Kuts, Anatoly (My University, 2021)
Доцільність використання солей полігексаметиленгуанідину (ПГМГ) як антисептика при виробництві спирту з крохмалевмісної сировини. У виробничих умовах досліджено його вплив на перебіг мікробіологічних і біохімічних процесів, якість напівфабрикатів і спирту та підтверджено ефективність препарату «ПГМГ» для пригнічення росту контамінативної мікрофлори. Expediency of the use of poliheksamethyleneguanidine (PHMG) salts is reasonable as the antiseptic in alcohol production from starch-containing raw materials. In working environment its influence on the course of microbiological and biochemical processes, quality of semiproducts and alcohol was investigated and efficiency of the preparation «PHMG» for inhibition of contaminating microflora growth was confirmed.
Keywords: спиртове виробництво; мікрофлора; антисептик; alcohol production; contaminating microflora; antiseptic; кафедра біотехнології продуктів бродіння і виноробства